Recognition helices of lac and lambda repressor are oriented in opposite directions and recognize similar DNA sequences. - Lehming, N (1988)
Exchanges in positions 1 and 2 of the putative recognition helix allow lac repressor to bind to ideal lac operator variants in which base pair 4 has been replaced. We show here that an Arg-22----Asn exchange in position 6 of the putative recognition helix of lac repressor abolishes lac repressor binding to ideal lac operator. This lac repressor variant, however, binds to a variant of the ideal lac operator 5' TTTGAGCGCTCAAA 3' in which the original G.C of position 6 has been replaced by T.A. This result and our previous data confirm our suggestion that the N terminus of the recognition helix of lac repressor enters the major groove close to the center of symmetry of lac operator and that its C terminus leaves the major groove further away from the center of symmetry. The consequences of this model are discussed in regard to various phage and bacterial repressor operator systems.